El trabajo en plataformas digitales y la legislación ecuatoriana. - Altamirano Poveda, Edgar David (2023)
Globalization and the implementation of tools such as information technologies brought with it the transformation of the labor market through digital platforms that offer products or services, creating jobs for the development of activities such as transport or home delivery, a labor situation that was strengthened after the global pandemic caused by Covid-19. In this way, the labor provisions in Ecuador were analyzed with a legal, doctrinal and comparative approach to determine if they are sufficient to regulate the work carried out on digital platforms. To achieve the proposed objective, historical-logical, legal-doctrinal, inductive, analytical, and descriptive methods were used; The research was basic, bibliographic, descriptive and analytical, non-experimental design, and qualitative approach; for the collection of information, interviews were applied with which it was determined that in Ecuador labor relations executed on digital platforms are not regulated, unlike other countries studied, the Ecuadorian case does not reflect a normative advance at the same time as the accelerated growth of work on digital platforms, in this way it was concluded that the current labor regulations are insufficient and consequently, Workers' rights and principles, such as job stability, social security, remuneration, and working hours, are violated.